Eriodictyol Suppresses Gastric Cancer Cells via Inhibition of PI3K/AKT Pathway - Hui Shan; Xin Zhang; Yalu Mi; Jihui Jia; Bo Wang; Qing Yang (Pharmaceuticals, 2022)
Gastric cancer (GC) is among the five most common malignancies worldwide. Traditional chemotherapy cannot efficiently treat the disease and faces the problems of side effects and chemoresistance. Polygoni orientalis Fructus (POF), with flavonoids as the main bioactive compounds, exerts anti-cancer potential. In this study, we compared the anti-GC effects of the main flavonoids from POF and investigated the anti-cancer effects of eriodictyol towards GC both in vitro and in vivo. CCK-8 assays were performed to examine the inhibitory effects of common flavonoids from POF on GC cell viability. Colony formation assays were used to determine cell proliferation after eriodictyol treatment. Cell cycle distribution was analyzed using flow cytometry. Induction of apoptosis was assessed with Annexin V/PI staining and measurement of related proteins. Anti-cancer effects in vivo were investigated using a xenograft mouse model. Potential targets of eriodictyol were clarified by network pharmacological analysis, evaluated by molecular docking, and validated with Western blotting. We found that eriodictyol exhibited the most effective inhibitory effect on cell viability of GC cells among the common flavonoids from POF including quercetin, taxifolin, and kaempferol. Eriodictyol suppressed colony formation of GC cells and induced cell apoptosis. The inhibitory effects of eriodictyol on tumor growth were also validated using a xenograft mouse model. Moreover, no obvious toxicity was identified with eriodictyol treatment. Network pharmacology analysis revealed that PI3K/AKT signaling ranked first among the anti-GC targets. The molecular docking model of eriodictyol and PI3K was constructed, and the binding energy was evaluated. Furthermore, efficient inhibition of phosphorylation and activation of PI3K/AKT by eriodictyol was validated in GC cells. Taken together, our results identify eriodictyol as the most effective anti-GC flavonoids from POF and the potential targets of eriodictyol in GC. These findings suggest that eriodictyol has the potential to be a natural source of anti-GC agents.